Effects of Medical Security Satisfaction and Trust in Doctors on Subjective Well-Being: Evidence from China - Gong, Xiaomei; Zhang, Jiaping (International Journal of Management and Sustainability, 2019)
How to improve residents’ well-being is regarded as an important goal of sustainable economic development. Although health care has an important impact (directly and indirectly) on subjective well-being (SWB), existing literature rarely empirically investigated the impact of individual’s satisfaction with health care on SWB, especially in developing countries like China, where the health care level has obviously lagged behind the public health needs and the speed of economic development. In addition, China is also facing a tense doctor-patient relationship situation in recent years. Based on the data from the Chinese Social Survey (CSS) for 2015, this paper empirically analyzes the impact of medical security satisfaction and trust in doctors (to reflect doctor-patient relationship) on Chinese people’s SWB. We have adopted a variety of methods for robust test, and used the propensity score matching (PSM) method to deal with the endogenous problems that may be caused by “selection bias”. The results show that both the medical security satisfaction and trust in doctors have positive effects on SWB, indicating that the improvement of medical security and doctor-patient relationship can contribute to Chinese people’s SWB in the new era. This study has certain guiding significance for the implementation of “healthy China” strategy, and further enriches the related research of health economics.